Eribulin Mesylate as Third or Subsequent Line Chemotherapy for Elderly Patients with Locally Recurrent or Metastatic Breast Cancer: A Multicentric Observational Study of GIOGer (Italian Group of Geriatric Oncology)‐ERIBE. (9th November 2018) - Leo, Silvana; Arnoldi, Ermenegildo; Repetto, Lazzaro; Coccorullo, Zaira; Cinieri, Saverio; Fedele, Palma; Cazzaniga, Marina; Lorusso, Vito; Latorre, Agnese; Campanella, Giovanna; Ciccarese, Mariangela; Accettura, Caterina; et al.
Abstract: Background: Metastatic breast cancer (MBC) is highly prevalent in middle‐aged or elderly patients. Eribulin is a nontaxane microtubule inhibitor, approved for the treatment of pretreated MBC. This multicentric study (sponsored by GIOGer, Italian Group for Geriatric Oncology) was designed to assess the efficacy and tolerability of eribulin, according to parameters usually used in geriatric oncology. Subjects, Materials, and Methods: An observational study was conducted on 50 consecutive elderly patients with MBC. The primary endpoint was to evaluate the change in items score of comprehensive geriatric assessment (CGA) and health‐related quality of life (HRQL). Italian versions of the CGA and HRQL questionnaires were administered at baseline, before the third and fifth cycles, and then every three cycles until treatment discontinuation. Secondary endpoints were efficacy and safety. Results: Overall, both EQ‐5D scores and EQ‐5D‐3 L visual analogic scale did not significantly change from baseline; the percentage of subjects without problems doing usual activities tended to decrease during treatment ( p for linear trend .018), and the percentage of patients with minor problems performing usual activities tended to increase ( p for linear trend.012). Among CGA items, Instrumental Activities of Daily Living tended to decrease during treatment and Geriatric Depression Scale tended to increase. After 12 months follow‐up, 24 patients (out of 47) showed clinical benefits; median progression‐free survival was 4.49 months (2.10–10.33) and median OS was 7.31 months (3.70–14.03). The treatment was associated with mild toxicity. Conclusion: Eribulin treatment preserved quality of life and geriatric parameters included in the CGA, except for instrumental functioning and geriatric depression, in elderly patients with MBC. Abstract : Results of a multi‐center study, designed to assess the use of eribulin in elderly patients with metastatic breast cancer, are reported.